An analysis of progressive sectors: agriculture position. Issue 1 (March 2021) - Arsyad, M; Yunus, S R; Lanuhu, N; Jamil, M H; Mahyuddin,; Alim, N
Abstract: In the economic development of a region, there needs to be attention in developing sectors that have the potential and also have good growth. This study aims to identify the economic sectors included in the progressive sector. This research uses secondary data in the form of Gross Regional Domestic Product (GRDP) of Bolaang Mongondow Regency and North Sulawesi Province in 2013-2017 and will then be analyzed using the Location Quotient method and Shift Share analysis. The results of the study concluded that there are five economic sectors which are the base sectors namely the Agriculture, Forestry, and Fisheries sectors; Mining and Excavation sectors, the Electricity and Gas Procurement Sector, Real Estate Sector and Education Services Sector. However, only the Mining and Excavation sector has a progressive growth rate and competitive advantage. As for the Agriculture position itself, it has a non-progressive growth rate and lacks a competitive advantage. In addition, there are four sectors namely the Construction sector, the Wholesale Trade, and Retail; Car and Motorcycle Repair sectors; The Financial Services and Insurance sectors and the Government Administration, Defense, and Social Security sectors are required to be able to move progressively even though those sectors are not included in the base sector.